The effects of a CAADP-compliant budget on poverty and inequality in Ghana - Younger, Stephen D.; Benin, Samuel (International Food Policy Research Institute, 2017)
Ghana has accepted the CAADP commitment to dedicate 10 percent of government spending to the agricultural sector. In a 2014 paper, Benin argues that Ghana falls short of that goal, and in a 2016 paper, Younger shows that despite the current fiscal crisis, there is fiscal space to meet the commitment. Benin estimates the rates of return to increased public expenditure on agriculture, finding that they are quite high, especially if the investments are made in the noncocoa sector. This paper uses Benin’s estimates to examine the poverty and inequality consequences of increasing public expenditure on agriculture. Key conclusions are that public expenditure on agriculture is surprisingly progressive, especially if spent in the grains subsector. This progressivity, combined with the high rate of return, means that public investment in agriculture may actually be more efficient at reducing poverty than LEAP, Ghana’s targeted conditional cash transfer program.